2019
DOI: 10.7759/cureus.4641
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum of Near-miss Cases in Obstetrics

Abstract: Introduction Near-miss obstetric cases are the ones which have survived childbirth after a life-threatening and complicated pregnancy. The aim of this study is to evaluate important characteristics and causes of near-miss cases, compare them with maternal deaths, and assess urgent interventions managing these patients. Materials and methods This prospective, cross-sectional study was conducted in the intensive care unit of the Obstetrics and Gynecology department. Clinical spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
3
6
1
1
Order By: Relevance
“…Another individual determinant for obstetric risk to consider is parity. Most authors suggest that multiparity is a risk factor for extreme maternal morbidity [26][27][28]. Although, there are authors who state that first time pregnancy is also a risk factor associated with this condition [29], we found no significant difference between history of being multiparous and primiparous for the development of an extreme maternal morbidity event ( X 2 =0.05, p= 0.9).…”
Section: Discussioncontrasting
confidence: 70%
“…Another individual determinant for obstetric risk to consider is parity. Most authors suggest that multiparity is a risk factor for extreme maternal morbidity [26][27][28]. Although, there are authors who state that first time pregnancy is also a risk factor associated with this condition [29], we found no significant difference between history of being multiparous and primiparous for the development of an extreme maternal morbidity event ( X 2 =0.05, p= 0.9).…”
Section: Discussioncontrasting
confidence: 70%
“…Table 4 highlights the comparison of MNM indicators from various studies. [ 9 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of a maternal near-miss was hypertensive disorder in this study, which was similar to the study done by Jain in 2019 [ 8 ] and the study by Mansuri et al [ 10 ] in Ahmadabad, Gujrat, in 2018, whereas the study by Bansal et al [ 7 ] in 2016 and Roopa et al [ 11 ] in 2013 showed hemorrhage as the most common SAMM followed by hypertensive disorders in pregnancy. Another study done by Sultana et al [ 12 ] in Karachi, Pakistan, showed hemorrhage, hypertensive disorder in pregnancy, and sepsis as the most common causes of near-miss events. Other studies done by Chikadaya et al [ 13 ] in Zimbabwe and by Dessalegn et al [ 14 ] in Ethiopia showed the most common cause of a near-miss as hemorrhage and hypertensive disorder in pregnancy followed by early pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%